Offshore Renewables for a Transition to a Low Carbon Society - Rusu, Liliana; Stratigaki, Vicky (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Taking into account the increasing general concern related to the necessity of reducing CO2 emissions, a very important aspect of this topic refers to the green energy sector. In this vein, the present Special Issue is focused on the area of Offshore Renewable Energy (ORE). This Special Issue contains valuable works related to ORE.